Delineating The Relationship Between Innovation Strategy And Strategic Planning on Small Firm - Lahcene Makhloufi; Farouk Djermani (STIM LASHARAN JAYA MAKASSAR, 2022)
The aim of this paper is to establish and delineate a relationship between innovation strategy and strategic planning toward firm performance based on both theories resource-based view and diffusion innovation theory. Successful firms are always aware to effectively implement these strategies as a powerful resource, in order to ensure its survival among current and potential rivals. Therefore, this paper review previous studies and find a critical gap in the literature, since very few studies that investigate the two variables as a strategic resource in single research hence, this paper will fill the emerged gap and provide several implications for policymakers and related stakeholders.